Teori dan Model Analisis Kebijakan Pendidikan - Fathoni, Wildan; Nasution, Imam Wahyudi; Yusup, Muhammad; Asiah, Nur; A, Amirudin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study discusses theories and models of educational policy analysis with a focus on their relevance in the context of national education and Islamic education in Indonesia. The review covers various educational management theories, such as systems theory, contingency theory, and change theory, to understand the dynamics and complexity of educational institution management. In addition, this research explores models of educational policy analysis, including the rational model, systems model, and CIPP model, and adopts a critical approach to identify assumptions, interests, and the impact of policies on diverse community groups. The method used is library research with a qualitative approach, analyzing primary and secondary data from various reliable sources. The results show that management theory is essential in formulating, implementing, and evaluating educational policies to create a generation that is faithful, pious, and prepared to face contemporary challenges. Case studies of educational policy in Indonesia highlight the need for a multidimensional and participatory approach to realize an educational system that is fair, inclusive, and of high quality.